Effect of dietary carbohydrate restriction on glycemic control in adults with diabetes: A systematic review and meta-analysis. (May 2018) - Sainsbury, Emma; Kizirian, Nathalie V.; Partridge, Stephanie R.; Gill, Timothy; Colagiuri, Stephen; Gibson, Alice A.
Highlights: Carbohydrate-restricted diets produce greater reductions in HbA1c over 3–6 months. The effects are primarily driven by low carbohydrate diets (<26% of total energy). Both diets showed declining effectiveness over the longer-term (12–24 months). Abstract: Nutrition therapy is considered a key component of diabetes management, yet evidence around the ideal macronutrient composition of the diet remains inconclusive. A systematic review and meta-analysis was performed to assess the effects of carbohydrate-restricted diets (≤45% of total energy) compared to high carbohydrate diets (>45% of total energy) on glycemic control in adults with diabetes mellitus. Six databases were searched for articles published between January 1980 and August 2016. Primary outcome was between-group difference in HbA1c change. Individual effect sizes were standardized, and a meta-analysis performed to calculate pooled effect size using random effects. 25 RCTs involving 2412 participants were included. Carbohydrate-restricted diets, in particular those that restrict carbohydrate to <26% of total energy, produced greater reductions in HbA1c at 3 months (WMD −0.47%, 95% CI: −0.71, −0.23) and 6 months (WMD −0.36%, 95% CI: −0.62, −0.09), with no significant difference at 12 or 24 months. There was no difference between moderately restricted (26–45% of total energy) and high carbohydrate diets at any time point. Although there are issues with the quality of the evidence, this review suggests that carbohydrate-restricted diets could be offered to people living with diabetes as part of an individualised management plan.